The digital reading condition - Engberg, Maria, 1971-; Have, Iben, 1970-; Stougaard Pedersen, Birgitte (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This volume offers a critical overview of digital reading practices and scholarly efforts to analyze and understand reading in the mediatized landscape. Building on research about digital reading, born digital literature, and digital audiobooks, The Digital Reading Condition explores reading as part of a broader cultural shift encompassing many forms of media and genres. Bringing together research from media and literary studies, digital humanities, scholarship on reading and learning, as well as sensory studies and research on multimodal and multisensory media reception, the authors address and challenge print-biased conceptions of reading that are still prevalent in research, whether the reading medium is print or digital. They argue that the act of reading itself is changing, and rather than rejecting digital media as not suitable for sustained or focused reading practices, argue that the complex media landscape challenges us to rethink how to define reading as a mediated practice. Presenting a truly interdisciplinary perspective on digital reading practices, this volume will appeal to scholars and graduate students in communication, media studies, new media and technology, literature, digital humanities, literacy studies, composition, and rhetoric"--
Introduction / Maria Engberg, Iben Have, and Birgitte Stougaard Pedersen -- Section I. Historical and Sociocultural Perspectives on Reading -- Introduction to Section I -- Reading and Materiality: Conditions of Digital Reading / Maria Engberg -- History of Media Cultures from the Perspective of Multisensory Reading / Iben Have -- The Condition of Reading in a Digital Media Culture / Jay David Bolter -- Reading Toward Multiliteracies: Understanding Reading Comprehension and Reading Experience / Birgitte Stougaard Pedersen and Iben Have -- Section II. Multisensory Reading -- Introduction to Section II -- Reading and the Senses: Cultural and Technological Perspectives / Birgitte Stougaard Pedersen and Maria Engberg -- Reading a Literary App for Children / Ayoe Quist Henkel -- Trends in Immersive Journalism / Iben Have and Maria Engberg -- Multisensory Reading of Digital Audiobooks / Iben Have and Birgitte Stougaard Pedersen -- How to Read a Network, or the Internet as Unfinished Demo / Lori Emerson -- Section III. Reading Engagement: Aspects of Digital Reading -- Introduction to Section III -- Deep, Focused, and Critical Reading Between Media / Maria Engberg and Birgitte Stougaard Pedersen -- Reading Digital Interfaces and Audiobooks: Media-Specific and Multisensory Aspects of Immersion / Ayoe Quist Henkel and Birgitte Stougaard Pedersen -- Motivations for Audiobook Reading in Modern Everyday Lives / Iben Have -- Section IV. Young Readers Between Media -- Introduction to Section IV -- Digital Reading in Education: A Situated Disciplinary Literacies Perspective / Nikolaj Elf -- Different Modes of Reading: Eighth-Grade Students' Interaction with a Digital Narrative / Signe Hjort Nielsen and Ayoe Quist Henkel -- Transmedial Reading / Susana Tosca -- Readers Between Media: Sixth-Grade Students Tuning in to Literature in Different Formats / Ayoe Quist Henkel -- Section V. Aesthetics and Digital Reading -- Introduction to Section V -- Situated Reading / Maria Engberg and Birgitte Stougaard Pedersen -- Reading: Atmosphere, Ambience, and Attunement / Birgitte Stougaard Pedersen -- Resonance and the Digital Conditions of Reading / Lutz Koepnic -- Conclusion: The Digital Reading Condition / Maria Engberg, Iben Have, and Birgitte Stougaard Pedersen.
Keywords: Books and reading -- Psychological aspects; Reading, Psychology of; Reading -- Technological innovations; Digital media; Intermediality; Literature and technology; LANGUAGE ARTS & DISCIPLINES / Communication; LANGUAGE ARTS & DISCIPLINES / Literacy